Healthy Diets and Lifestyles in the World: Mediterranean and Blue Zone People Live Longer. Special Focus on Gut Microbiota and Some Food Components - Santacroce, Luigi; Bottalico, Lucrezia; Charitos, Ioannis Alexandros; Haxhirexha, Kastriot; Topi, Skender; Jirillo, Emilio (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2024)
Longevity has been associated with healthy lifestyles, including some dietary regimens, such as the Mediterranean diet (MedDiet) and the Blue Zone (BZ) diets. MedDiet relies on a large consumption of fruit, vegetables, cereals, and extra-virgin olive oil, with less red meat and fat intake. Four major BZ have been recognized in the world, namely, Ogliastra in Sardinia (Italy), Ikaria (Greece), the Peninsula of Nicoya (Costa Rica), and Okinawa (Japan). Extreme longevity in these areas has been associated with correct lifestyles and dietary regimens. Fibers, polyphenols, beta-glucans, and unsaturated fatty acids represent the major constituents of both MedDiet and BZ diets, given their anti-inflammatory and antioxidant activities. Particularly, inhibition of the NF-kB pathway, with a reduced release of pro-inflammatory cytokines, and induction of T regulatory cells, with the production of the anti-inflammatory cytokine, interleukin-10, are the main mechanisms that prevent or attenuate the “inflammaging.” Notably, consistent physical activity, intense social interactions, and an optimistic attitude contribute to longevity in BZD areas. Commonalities and differences between MedDIet and BZ diets will be outlined, with special reference to microbiota and food components, which may contribute to longevity.
Keywords: Aging